The Application of Artificial Compound Eye in Precision Guided Munitions for Urban Combat - Song, Yan-feng; Hao, Qun; Cao, Jie; Liu, Qiang-hui; Liu, Hao; Li, Jie (Journal of physics. Conference series, 2023)
As an ideal visual perception system with miniaturization, multi-aperture, wide field of view, low aberration, infinite depth of field, high efficiency and real-time, bionic compound eye has obvious intelligent characteristics, which provides a new idea for the future intelligent development of precision guided weapons, and has also been highly concerned by the US military. Under the leadership of the military, the United States has carried out a series of studies and achieved a series of results. The strategic position of urban combat in the future is analyzed. The requirements of the U.S. Air Force for the next generation of precision-guided munitions, and also the strategic significance of developing urban combat weapons and equipment is described. The advantages and characteristics of artificial compound eye are briefly described. Mainly discussed a series of WFOV artificial compound eye seeker being studied and developed by the U.S. Air Force for urban warfare, as well as the research and development process. Finally, the development suggestion of the WFOV artificial compound eye seeker is given.